2014
DOI: 10.1111/all.12439
|View full text |Cite
|
Sign up to set email alerts
|

Quantity and diversity of environmental microbial exposure and development of asthma: a birth cohort study

Abstract: BackgroundEarly-life exposure to environmental microbial agents may be associated with the development of allergies. The aim of the study was to identify better ways to characterize microbial exposure as a predictor of respiratory symptoms and allergies.MethodsA birth cohort of 410 children was followed up until 6 years of age. Bacterial endotoxin, 3-hydroxy fatty acids, N-acetyl-muramic acid, fungal extracellular polysaccharides (EPS) from Penicillium and Aspergillus spp., β-D-glucan, ergosterol, and bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
55
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 28 publications
7
55
3
Order By: Relevance
“…The 10 targets were simultaneously analyzed and provided essential information about the microbiology of different dwellings. It is for this reason that our study is original with respect to those that target only fungi communities (Reponen et al, 2013;Reponen et al, 2011;Vesper et al, 2007b;Vesper et al, 2007c) or studies which characterized cumulative microorganism exposure (Ege et al, 2011;Karvonen et al, 2014;Roussel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 10 targets were simultaneously analyzed and provided essential information about the microbiology of different dwellings. It is for this reason that our study is original with respect to those that target only fungi communities (Reponen et al, 2013;Reponen et al, 2011;Vesper et al, 2007b;Vesper et al, 2007c) or studies which characterized cumulative microorganism exposure (Ege et al, 2011;Karvonen et al, 2014;Roussel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the PARSIFAL study (Ege et al, 2011;Schram-Bijkerk et al, 2005), dust endotoxins, Aspergillus and Penicillium extracellular polysaccharides and β-1,3-glucan levels were higher in control children's dwellings than in wheezers' homes. In the PASTURE study (Karvonen et al, 2014), children exposed to molds, bacteria and/or endotoxins developed fewer allergic diseases than children less exposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have established environmental exposures that can increase or decrease a child’s risk of developing asthma and/or atopy. Factors that decrease risk include growing up on farms, consumption of raw milk, and exposure to microbial products early in life (26). One recent epidemiological study of over 8000 children found exposure to specific types of farming, including exposure to hay, pigs, and poultry, provided protection from asthma (7).…”
Section: Introductionmentioning
confidence: 99%
“…30 Taken together, our current and previous findings can be seen as surrogates from a rich microbial exposure, which is inversely associated with the development of asthma. 31 A key strength of this study was the objectively inspectorbased report of moisture damage and mold within the homes using standardized methods. Moreover, this is the first prospective study looking at early age exposure to moisture damage and mold in relation to inflammatory markers among children assessed in later childhood.…”
mentioning
confidence: 99%